Qualitative experiences of breast cancer survivors on a self-management intervention: 2-year post-intervention - Ng, L.L. (2011)
Background: Increasing survivorship warrants evidence-based intervention to help women manage living effectively with breast cancer. Breast cancer survivors may have many medical and psychosocial issues in the post-treatment period. Qualitative research was carried out to assess survivors 19 overall experience and if intervention helps in survivorship care. This paper reports exploration of benefit-findings from participation in an earlier 4-week self management intervention. Methods: We used a grounded theory approach to analyze three focus groups conducted between May and August 2010 in Kuala Lumpur. We used random sampling to recruit the informants (n=21), all of whom had earlier participated in the 4 week self-management program held two years previously. Findings: The women reported positive experience and growth with the self management program. Self-efficacy appears as an important underlying theme for successful experiences. The lack of proactive plans to provide bereavement support to surviving women was a key negative experience. Conclusion: The intervention successfully brought women together to work in close partnership with health professionals on ways to self manage the medical, emotional and role task as they live indefinitely with breast cancer, a new chronic illness. The beneficial effect from the 4 week intervention was expressed by women even at 2 years after the program. Having successfully developed a tightly knitted group, a major oversight was the lack of professional support on bereavement for grieving members when close friends passed away.